Different gDNA content in the subpopulations of prostate cancer extracellular vesicles: Apoptotic bodies, microvesicles, and exosomes - Lázaro-Ibáñez, Elisa; Sanz-Garcia, Andres; Visakorpi, Tapio; Escobedo-Lucea, Carmen; Siljander, Pia; Ayuso-Sacido, Ángel; Yliperttula, Marjo (The Prostate, 2014)
BACKGROUND Extracellular vesicles (EVs) are cell‐derived membrane vesicles. EVs contain several RNAs such as mRNA, microRNAs, and ncRNAs, but less is known of their genomic DNA (gDNA) content. It is also unknown whether the DNA cargo is randomly sorted or if it is systematically packed into specific EV subpopulations. The aim of this study was to analyze whether different prostate cancer (PCa) cell‐derived EV subpopulations (apoptotic bodies, microvesicles, and exosomes) carry different gDNA fragments. METHODS EV subpopulations were isolated from three PCa cell lines (LNCaP, PC‐3, and RC92a/hTERT) and the plasma of PCa patients and healthy donors, and characterized by transmission electron microscopy, nanoparticle tracking analysis and total protein content. gDNA fragments of different genes were detected by real time quantitative PCR and confirmed by DNA sequencing. RESULTS We report that the concentration of EVs was higher in the cancer patients than in the healthy controls. EV subpopulations differed from each other in terms of total protein and DNA content. Analysis of gDNA fragments of MLH1, PTEN, and TP53 genes from the PCa cell‐derived EV subpopulations showed that different EVs carried different gDNA content, which could even harbor specific mutations. Altogether, these results suggest that both nucleic acids and proteins are selectively and cell‐dependently packed into the EV subtypes. CONCLUSIONS EVs derived from PCa cell lines and human plasma samples contain double‐stranded gDNA fragments which could be used to detect specific mutations, making EVs potential biomarkers for cancer diagnostics and prognostics. Prostate 74:1379–1390, 2014. © 2014 The Authors. The Prostate published by Wiley Periodicals, Inc.